Communication-Efficient String Sorting - Bingmann, Timo; Sanders, Peter; Schimek, Matthias (Proceedings - IEEE International Parallel and Distributed Processing Symposium, 2020)
There has been surprisingly little work on algorithms for sorting strings on distributed-memory parallel machines. We develop efficient algorithms for this problem based on the multi-way merging principle. These algorithms inspect only characters that are needed to determine the sorting order. Moreover, communication volume is reduced by also communicating (roughly) only those characters and by communicating repetitions of the same prefixes only once. Experiments on up to 1280 cores reveal that these algorithm are often more than five times faster than previous algorithms.